PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIRTUAL TOUR SEBAGAI SUMBER BELAJAR IPS KEARIFAN LOKAL ARCA JOKO DOLOG DI KOTA SURABAYA - Indra Febry Nandiansyah; Sukma Perdana Prasetya; Agus Suprijono; Hendri Prastiyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The use of digital learning media in Social Studies (IPS) instruction remains limited, resulting in teacher-centered learning and insufficient contextual learning experiences for students. This study aimed to develop a Virtual Tour-based learning media featuring the Joko Dolog Statue as a local wisdom-based learning resource for Social Studies and to examine its feasibility and effectiveness in improving students' learning outcomes. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of the stages of analyze, design, development, implementation, and evaluation. The participants were 35 eighth-grade students of SMP Islam Shafta Surabaya in the 2026/2027 academic year. Data were collected through observations, interviews, questionnaires, and learning achievement tests. Data analysis was conducted using descriptive statistics, a paired sample t-test, and the N-Gain index. The results indicated that the developed media met the feasibility criteria based on expert validation. Student and teacher responses reached 84.36% and 93.75%, respectively, both categorized as very good. The mean score increased from 58.71 on the pretest to 85.57 on the posttest. The N-Gain score of 0.70 indicated that the media was moderately effective, while the paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant improvement in learning outcomes after the implementation of the media. These findings demonstrate that the Virtual Tour-based Joko Dolog learning media is feasible and effective as a local wisdom-based Social Studies learning resource to enhance students' learning outcomes.